Cistanche tubulosa phenylethanoid glycosides suppressed adipogenesis in 3T3-L1 adipocytes and improved obesity and insulin resistance in high-fat diet induced obese mice - Dilinazi Abudujilile; Weilan Wang; Alimu Aimaier; Lili Chang; Yuliang Dong; Yiye Wang; Xu Fan; Yu Ma; Yongli Wang; Dilinigeer Ziyayiding; Yuan Ma; Jie Lv; et al. (BMC, 2022)
Abstract Background Cistanche tubulosa is an editable and medicinal traditional Chinese herb and phenylethanoid glycosides are its major components, which have shown various beneficial effects such as anti-tumor, anti-oxidant and neuroprotective activities. However, the anti-obesity effect of C. tubulosa phenylethanoid glycosides (CTPG) and their regulatory effect on gut microbiota are still unclear. In the present study, we investigated its anti-obesity effect and regulatory effect on gut microbiota by 3T3-L1 cell model and obesity mouse model. Methods 3T3-L1 adipocytes were used to evaluate CTPG effects on adipogenesis and lipids accumulation. Insulin resistant 3T3-L1 cells were induced and used to measure CTPG effects on glucose consumption and insulin sensitivity. High-fat diet (HFD)-induced C57BL/6 obese mice were used to investigate CTPG effects on fat deposition, glucose and lipid metabolism, insulin resistance and intestinal microorganism. Results In vitro data showed that CTPG significantly decreased the triglyceride (TG) and non-esterified fatty acid (NEFA) contents of the differentiated 3T3-L1 adipocytes in a concentration-dependent manner without cytotoxicity, and high concentration (100 µg/ml) of CTPG treatment dramatically suppressed the level of monocyte chemoattractant protein-1 (MCP-1) in 3T3-L1 mature adipocytes. Meanwhile, CTPG increased glucose consumption and decreased NEFA level in insulin resistant 3T3-L1 cells. We further found that CTPG protected mice from the development of obesity by inhibiting the expansion of adipose tissue and adipocyte hypertrophy, and improved hepatic steatosis by activating AMPKα to reduce hepatic fat accumulation. CTPG ameliorated HFD-induced hyperinsulinemia, hyperglycemia, inflammation and insulin resistance by activating IRS1/Akt/GLUT4 insulin signaling pathway in white adipose tissue. Moreover, gut microbiota structure and metabolic functions in HFD-induced obese mice was changed by CTPG, especially short chain fatty acids-producing bacteria including Blautia , Roseburia , Butyrivibrio and Bacteriodes were significantly increased by CTPG treatment. Conclusions CTPG effectively suppressed adipogenesis and lipid accumulation in 3T3-L1 adipocytes and ameliorated HFD-induced obesity and insulin resistance through activating AMPKα and IRS1/AKT/GLUT4 signaling pathway and regulating the composition and metabolic functions of gut microbiota.